Data from: Stocking activities for the Arctic charr in Lake Geneva: genetic effects in space and time - Savary, Romain; Dufresnes, Christophe; Champigneulle, Alexis; Caudron, Arnaud; Dubey, Sylvain; Perrin, Nicolas; Fumagalli, Luca (Zenodo, 2018)
Artificial stocking practices are widely used by resource managers worldwide, in order to sustain fish populations exploited by both recreational and commercial activities, but their benefits are controversial. Former practices involved exotic strains, although current programs rather consider artificial breeding of local fishes (supportive breeding). Understanding the complex genetic effects of these management strategies is an important challenge with economic and conservation implications, especially in the context of population declines. In the present study, we focus on the declining Arctic charr (Salvelinus alpinus) population from Lake Geneva (Switzerland and France), which has initially been restocked with allochtonous fishes in the early eighties, followed by supportive breeding. In this context, we conducted a genetic survey to document the evolution of the genetic diversity and structure throughout the last 50 years, before and after the initiation of hatchery supplementation, using contemporary and historical samples. We show that the introduction of exotic fishes was associated with a genetic bottleneck in the 1980-1990s, a break of Hardy-Weinberg Equilibrium (HWE), a reduction of genetic diversity, an increase of genetic structure among spawning sites, and a change in their genetic composition. Together with better environmental conditions, three decades of subsequent supportive breeding using local fishes allowed to re-establish HWE and the initial levels of genetic variation. However, current spawning sites have not fully recovered their original genetic composition and were extensively homogenized across the lake. Our study demonstrates the drastic genetic consequences of different restocking tactics in a comprehensive spatio-temporal framework, and suggests that genetic alteration by non-local stocking may be partly reversible through supportive breeding. We recommend that conservation-based programs consider local diversity and implement adequate protocols to limit the genetic homogenization ...